Caracterización del proceso inclusión/exclusión en jóvenes universitarios de la Carrera de Pedagogía - Piedra Zuriaga, Ronald Alberto (2018)
The present case study is about the different kinds of inclusion and exclusion that exist within the Career of Pedagogy at the Salesian Polytechnic University (U.P.S), therefore the goal of this case study is to recognize and identify the inclusion and exclusion practices within the University. This work hopes to respond to the following question: Which inclusion and exclusion practices do the Pedagogy students at the Salesian Polytechnic University engage in? The process allowed for a fieldwork where qualitative research was executed using the interview method, thus creating a dialogue that allowed to recognize how students perceive the subject in question in regards to their experiences at the university. It is important to mention that during the research process several interviews were likely applied to the students and to the professors at the Salesian Polytechnic University (Girón). The dominant results obtained from the case study were exclusion based on the socio and laboral structure, the Exclusion / Inclusion by Mass Media, Exclusion based on Culture, Exclusion based on fashion, Exclusion based on career choice or major, Intercultural Inclusion, and Socioeconomic Inclusion. On the other hand, you can also observe the interactions between the students and teachers at U.P.S, which demonstrate Inclusion / Exclusion based on Sexual Preferences and the Inclusion of People with disabilities among other tendencies.